Dopaminergic cells, derived from a high efficiency differentiation protocol from umbilical cord derived mesenchymal stem cells, alleviate symptoms in a Parkinson's disease rodent model. (21st January 2013) - Shetty, Prathibha; Thakur, Anirban M.; Viswanathan, Chandra
Abstract Mesenchymal stem cells (MSCs) could be an alternative to foetal cells in the treatment of several neurodegenerative diseases, especially Parkinson's disease (PD). We have previously demonstrated the functional efficacy of the undifferentiated bone marrow MSCs (BMMSCs) cultured in a xenofree conditions in PD animal models. We now demonstrate isolation of MSCs from the umbilical cord matrix tissue and assess their safety and efficacy to improve Parkinsonian symptoms in an in vivo animal model. The efficacy of MSCs from BM and umbilical cord in the PD animal mode has also been studied, and more importantly the efficacy of using differentiated UCMSC (D‐UCMSCs) to dopaminergic phenotype. Phenotypically, UCMSCs expressed higher levels of SSEA4 compared to BMMSCs. Analysis of differentiated cells showed that D‐UCMSCs expressed significant levels of Tyrosine Hydroxyalse and Nurr1 compared to D‐BMMSCs. The in vivo efficacy of the differentiated and undifferentiated cell types in the Parkinsonian rats showed that D‐UCMSCs improved the symptoms throughout a year of study. Differentiated cell types are potentially better for clinical use than the undifferentiated type, provided they are made available at the site of action in adequate numbers. MSCs are less immunogenic and immunomodulatory, which opens up the further possibility of using these cells in allogeneic settings. This could be a novel cell therapy application, especially when getting autochthonous cells is difficult.